Estimacion del volumen comercial a diametros y alturas variables para Tectona grandis L.F. en Costa Rica - Pérez Cordero, L.D.; Kanninen, M. (2003)
Estimation of the commercial volume to diameters and variable heights for Tectona grandis L.F. in Costa Rica. Management practices for Tectona grandis have improved during the last decade. However, accurate volume equations are not available yet. The aim of this study was to test equations which best predict individual-tree total volume and merchantable volume (at variable top diameter and top height) for T. grandis in Costa Rica. A total of 112 trees with ages between 2 and 47 years and breast height diameter (DBH) between 2.4 and 58.7 cm were felled for the testing of the equations. The equations tested in this study fitted well the observed data. Other models, tested elsewhere, tended to overestimate the stem volume, especially at DBH ³ 30 cm. Model validation with independent data suggested that the models should be calibrated with local data if high accuracy is required (error less than 10%).